A importância da iniciação científica na formação de professores pesquisadores de química no ensino médio - Melo, Izabelly Menino (2013)
This conclusion paper describes the importance of Scientific Initiation for the formation of a qualified high school teacher. This theme was chosen to express the importance of forming a teacher with a wide vision for issues related to chemistry, in order to innovate their experiences and language as they ministry in the classroom and laboratory. The methodology used was the correlation of the Curriculum Guidelines in Chemistry , three experiments and the scientific initiation of the authors of this paper . With the rapid growth of knowledge in the last years , it’s mostly impossible for traditional teaching to be limited exclusively to the oral transmission of information . To get the attention of the students , teaching should be interactive, the teacher should design inexpensive experiments and of easy access ( considering that the reality the science laboratories in many schools is precarious ) , so that it will facilitate the understanding of the topics proposed by the Curriculum Guidelines of Chemistry and still have interdisciplinarity with other school subjects.